2022
DOI: 10.1111/nph.17977
|View full text |Cite
|
Sign up to set email alerts
|

SlWRKY35 positively regulates carotenoid biosynthesis by activating the MEP pathway in tomato fruit

Abstract: Summary Carotenoids are vital phytonutrients widely recognised for their health benefits. Therefore, it is vital to thoroughly investigate the metabolic regulatory network underlying carotenoid biosynthesis and accumulation to open new leads towards improving their contents in vegetables and crops. The outcome of our study defines SlWRKY35 as a positive regulator of carotenoid biosynthesis in tomato. SlWRKY35 can directly activate the expression of the 1‐deoxy‐d‐xylulose 5‐phosphate synthase (SlDXS1) gene to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 68 publications
(95 reference statements)
6
46
1
1
Order By: Relevance
“…Recently, in addition to traditional microbial chassis, using plants as hosts to produce high-value metabolites has become a new trend [ 16 ]. Tomato ( Solanum lycopersicum ) is an ideal chassis for plant engineering of carotenoids due to the abundance of isoprenoid precursors in the red fruit tissues [ 17 , 18 ]. The degradation of chlorophyll as well as the accumulation of carotenoids, including lycopene and β-carotene, determine the characteristic red coloration of ripening tomato fruits [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in addition to traditional microbial chassis, using plants as hosts to produce high-value metabolites has become a new trend [ 16 ]. Tomato ( Solanum lycopersicum ) is an ideal chassis for plant engineering of carotenoids due to the abundance of isoprenoid precursors in the red fruit tissues [ 17 , 18 ]. The degradation of chlorophyll as well as the accumulation of carotenoids, including lycopene and β-carotene, determine the characteristic red coloration of ripening tomato fruits [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The engineering of the metabolic pathway in tomato fruit is a promising strategy to overcome the physiological block of lutein and zeaxanthin biosynthesis, as has been performed in other plants [ [25] , [26] , [27] ]. Our previous study has shown that overexpression of SlLCYE alone can significantly increase lutein production in tomato fruit [ 17 ]. In this study, by using a combinatorial approach in the GoldenBraid 2.0 assembly system, we designed another three binary constructs containing different combinations of four endogenous synthetic genes of lutein and zeaxanthin pathway, encoding SlLCYE , SlLCYB , SlHYDB , and SlHYDE under the control of fruit specific promoters pE8 or p2A11 respectively, for generating lutein or zeaxanthin enriched tomato fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Quality control samples (QC) prepared by mixing all sample extracts were inserted every 10 samples to monitor the repeatability of the analysis process. UPLC separation was performed with the same protocol as Yuan et al [ 55 ]. Mass spectrographic analysis was performed by a triple quadrupole–linear ion trap mass spectrometer equipped with an ESI Turbo Ion−Spray interface (Applied Biosystems 4500 Q TRAP UPLC/MS/MS System), which operated according to a previous study [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…NAC family transcription factors, including NOR and NOR-like1 positively modulate biosynthetic pathway of ethylene and carotenoid by directly binding to the promoter of ACS2 and SlGGPPS2 [19,20]. Furthermore, other transcription factors such as CNR, AP2a, SlHB1, SlERF6, SGR1 as well as some WRKY transcription factors including SlWRKY35 and SlWRKY32 are also involved in ethylene biosynthesis and carotenoid accumulation during tomato fruit ripening [21][22][23][24][25][26][27][28]. The regulatory mechanism of ethylene in ripening of climacteric fruit, represented by tomato, has been well elucidated.…”
Section: Introductionmentioning
confidence: 99%